2019
DOI: 10.1088/1674-1056/ab3e67
|View full text |Cite
|
Sign up to set email alerts
|

Boundary states for entanglement robustness under dephasing and bit flip channels*

Abstract: We investigate the robustness of entanglement for a multiqubit system under dephasing and bit flip channels. We exhibit the difference between the entanglement evolution of the two forms of special states, which are locally unitarily equivalent to each other and therefore possess precisely the same entanglement properties, and demonstrate that the difference increases with the number of qubits n. Moreover, those two forms of states are either the most robust genuine entangled states or the most fragile ones, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al [15] have systematically investigated the speed of disentanglement for twoqubit arbitrary states and three-qubit pure states under depolarizing channel and found that GHZ-type states are the most robust. Several studies [16][17][18][19][20] have been devoted to the investigation of the robustness of multiqubit states which are locally unitarily equivalent to each other and therefore initially contain the same amount of entanglement. Borras et al [16] have investigated the decay of entanglement of multiqubit states that are equivalent to GHZ states under local unitary transformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [15] have systematically investigated the speed of disentanglement for twoqubit arbitrary states and three-qubit pure states under depolarizing channel and found that GHZ-type states are the most robust. Several studies [16][17][18][19][20] have been devoted to the investigation of the robustness of multiqubit states which are locally unitarily equivalent to each other and therefore initially contain the same amount of entanglement. Borras et al [16] have investigated the decay of entanglement of multiqubit states that are equivalent to GHZ states under local unitary transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In each of these decoherence processes, they proved the most robust genuine tripartite entangled states and the most fragile ones. Li et al [18] have investigated the robustness of multiqubit states under dephasing and bit flip channels and showed the difference between the entanglement evolution of the states of the two special forms, which are locally unitarily equivalent to each other. Pan et al [19]…”
Section: Introductionmentioning
confidence: 99%
“…Quantum entanglement is one of the most quintessential features of quantum mechanics, which distinguishes the quantum world from the classical one and plays essential roles in quantum information processing, [1][2][3][4][5] revealing the basic understanding of the nature of quantum correlations. One distinct property of quantum entanglement is that a quantum system entangled with another system limits its sharing with other systems, known as the monogamy of entanglement.…”
Section: Introductionmentioning
confidence: 99%